2016
DOI: 10.1007/s11427-016-5074-x
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary direction of processed pseudogenes

Abstract: While some pseudogenes have been reported to play important roles in gene regulation, little is known about the possible relationship between pseudogene functions and evolutionary process of pseudogenes, or about the forces responsible for the pseudogene evolution. In this study, we characterized human processed pseudogenes in terms of evolutionary dynamics. Our results show that pseudogenes tend to evolve toward: lower GC content, strong dinucleotide bias, reduced abundance of transcription factor binding mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Using our computational model, we obtained distribution patterns of nucleosome occupancy around both ends of pseudogenes in the human genome [39], which are in agreement with the experimental results. Analyses based on the model also indicated that processed pseudogenes show a decreased ability to form nucleosomes during evolution [40]. Possible applications of the model in the prediction of nucleosome free energy and nucleosome sliding were discussed [41].…”
Section: Introductionmentioning
confidence: 99%
“…Using our computational model, we obtained distribution patterns of nucleosome occupancy around both ends of pseudogenes in the human genome [39], which are in agreement with the experimental results. Analyses based on the model also indicated that processed pseudogenes show a decreased ability to form nucleosomes during evolution [40]. Possible applications of the model in the prediction of nucleosome free energy and nucleosome sliding were discussed [41].…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of selective pressure for their retention, TFBMs degenerate over evolutionary time. [ 91 ] Under selection, processed pseudogenes could evolve promoter activity and profoundly impact the coding sequences of nearby genes or host genes. For example, some pseudogene transcripts are embedded with alternative downstream transcriptional start sites inherited from parental transcripts that can evolve promoter activity.…”
Section: Pseudogenes Can Evolve Proto‐promoter Activity and Influence Proximal Genesmentioning
confidence: 99%